2017
DOI: 10.1039/c7cp04244b
|View full text |Cite
|
Sign up to set email alerts
|

Underpotential deposition of Cu on Au(111) from neutral chloride containing electrolyte

Abstract: Highly ordered: a commensurate (5 × 5) overlayer of chloride on top of a (1 × 1) pseudomorphic monolayer of copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…Isolated dimers were also tested in unit cells of 7 × 7 uc surface area. It was observed that the preferred position of copper adatoms on the Au(1 1 1) surface is in the three-fold hollow site, in good agreement with previous literature [60]. Adsorption on bridge and on top sites were found energetically more costly, by 0.03 eV and 0.8 eV respectively.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Isolated dimers were also tested in unit cells of 7 × 7 uc surface area. It was observed that the preferred position of copper adatoms on the Au(1 1 1) surface is in the three-fold hollow site, in good agreement with previous literature [60]. Adsorption on bridge and on top sites were found energetically more costly, by 0.03 eV and 0.8 eV respectively.…”
Section: Methodssupporting
confidence: 89%
“…In fact, upon dosing copper on Au(1 1 1), copper atoms incorporate into Au(1 1 1) [18][19][20]31,[43][44][45], then react with BTAH and are segregated to the surface [20,31]. Related systems considering the behaviour of Cu/Au(1 1 1) [20,[44][45]60], the adsorption of BTAH on copper single crystals [26][27][28][29][30]66], on Au(1 1 1) [65], and on Cu/Au(1 1 1) [31], to which comparison will be made, have been investigated separately elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions of experimental studies are supplemented and verified by theoretical methods such as statistical mechanics, Monte Carlo simulation, and density functional theory. 23,48,49 The studies on the role of chloride ions in Cu UPD have attracted extensive attention due to their significant and complicated effect on the process. In 1990, Magnussen et potential control, which revealed the structural change from (√3 × √3) R30°to (5 × 5) during the process of Cu UPD.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to prepare solid materials with well-dened structures have gathered tremendous interest in physics, 1 chemistry, 2,3 materials science, [4][5][6] and the semiconductor industry. 7,8 For a metal, a variety of properties depend critically on its crystal structure, 9 including electricity, [10][11][12] transparency, 13 and catalysis. 14,15 In the past decades, various methods have been developed to fabricate metal crystals with distinct structures, such as liquid-phase crystal growth, 16,17 programmed annealing, 18 and epitaxial lm deposition.…”
Section: Introductionmentioning
confidence: 99%